Lack of evidence for human infection with Xenotropic murine leukemia virus-related virus in the Brazilian Amazon basin - GOMES, Samara Tatielle Monteiro (2014)
Introduction: This study confirmed the absence of natural infection with Xenotropic murine leukemia virus-related virus (XMRV) or XMRV-related disease in human populations of the Brazilian Amazon basin. We demonstrated that 803 individuals of both sexes, who were residents of Belem in the Brazilian State of Pará, were not infected with XMRV. Methods: Individuals were divided into 4 subgroups: healthy individuals, individuals infected with human immunodeficiency virus, type 1 (HIV-1), individuals infected with human T-lymphotrophic virus, types 1 or 2 (HTLV-1/2), and individuals with prostate cancer. XMRV infection was investigated by nested PCR to detect the viral gag gene and by quantitative PCR to detect pol. Results: There was no amplification of either gag or pol segments from XRMV in any of the samples examined. Conclusions: This study supports the conclusions of the studies that eventually led to the retraction of the original study reporting the association between XMRV and human diseases.